Amendments fail to hasten biocrust recovery or soil stability at a disturbed dryland sandy site. Issue 2 (3rd September 2018) - Chandler, David G.; Day, Natalie; Madsen, Matthew D.; Belnap, Jayne
Abstract : In most drylands, biological soil crusts (biocrusts), an assemblage of lichens, bryophytes, fungi, green algae, and cyanobacteria, are critical to healthy ecosystem function. However, they are extremely sensitive to disturbance and attempts to facilitate their recovery have had variable success. In this study, we applied soil amendments designed to improve soil surface stability and accelerate biocrust recovery on an area disturbed by oil/gas exploration vehicles. Treatments included: (1) control (one time water only); (2) biocrust‐only: biocrust inoculum + nutrients in water; (3) polyacrylamide gels (which are known to stabilize soils) + biocrust inoculum + nutrients in water; (4) gypsum + biocrust inoculum + nutrients in water; and (5) saline (NaCl) solution + biocrust inoculum + nutrients in water. Only the NaCl treatment showed any effects on soil properties and these were only short term. These effects included an increase in soil strength and a reduction in soil aggregate stability, unsaturated hydraulic conductivity ( K h ), and cyanobacterial biomass. The inoculated biocrust material failed to develop and even after 10 years, there was only a very low natural recolonization of the plots. These results show that inoculating soils or applying these levels of soil amendments does not guarantee recovery of soil stability or biocrust, and that some sites are unlikely to recover without assistance. Thus, there is a need for more research into ways to enhance soil stability and identify the factors limiting biocrust establishment.